PERANAN MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH YANG EFEKTIF UNTUK MENINGKATKAN MUTU PENDIDIKAN - Syahriza Arif Lubis; Sarah Aisah, Suci Nabilah, Adrian Muhamad Reza Pahlevi, Siti Ifa Faujiah, Atep Iman (CV. ADIBA AISHA AMIRA, 2024)
Principal leadership is needed to improve the quality of education in the school environment. This research raises the issue of Effective Principal Leadership Management on Education Quality. The purpose of this research is to find out the effective role of school principals to improve the quality of education. This research uses qualitative research methods of literature study. Qualitative research produces descriptive data in the form of written words. Principal leadership is the principal's effort to influence, encourage, guide, direct, and mobilize education personnel, parents, and school residents, to participate in order to achieve predetermined goals, namely improving the quality of education in schools. The principal's role as educator, manager, administrator, supervisor, and applying entrepreneurial values in managing educational institutions by innovating and developing schools can improve the quality of education in the institutions he leads.